Circular RNA circ_RANBP9 exacerbates polycystic ovary syndrome via microRNA-136-5p/XIAP axis. Issue 1 (1st January 2021) - Lu, Xiaohui; Gao, Haijie; Zhu, Bo; Lin, Guilan
ABSTRACT: Polycystic ovary syndrome (PCOS) is an endocrine disease that affects the health of many women. Circular RNAs (circRNAs) are associated with the occurrence and progression of PCOS. This study aimed to explore the function of circ_RANBP9 in PCOS. First, the circ_RANBP9 level was found to be increased in the plasma of patients with PCOS and ovarian granulosa cells (GCs) using Reverse Transcription-Quantitative Polymerase Chain Reaction (RT-qPCR). In GCs, loss of circ_RANBP9 decelerated proliferation and accelerated apoptosis of KGN and COV434 cells, as determined by MTT assay, colony formation assay, and flow cytometry. Furthermore, bioinformatics analysis showed that circ_RANBP9 and XIAP can be targeted by the microRNA, miR-136-5p. Luciferase reporter assay and RNA pull-down assay further verified the interaction between miR-136-5p and circ_RANBP9 or XIAP . Importantly, knockdown of circ_RANBP9 suppressed proliferation and promoted apoptosis of KGN and COV434 cells, whereas inhibition of miR-136-5p reversed these effects. Additionally, XIAP abolished the repression of proliferation and acceleration of apoptosis induced by miR-136-5p. The promotion of apoptosis was accompanied by upregulation of caspase-3 and Bax, and downregulation of Bcl-2, as estimated by western blotting. In conclusion, silencing of circ_RANBP9 inhibited GC proliferation and facilitated apoptosis by mediating the miR-136-5p/ XIAP pathway. These findings provide a new theoretical basis for screening and treatment of PCOS.